The impact of new teacher induction programs on feelings of burnout of special education teachers - Veatch, Julie M. (Kansas State University, 2006)
This study investigated the effects of new teacher induction programs on feelings of burnout of 69 newly hired special education teachers from two Midwestern, metropolitan school districts. The central research question was whether there was a significant difference in feelings of burnout between new teachers in a district that uses a special education instructional resource teacher as a key feature of their induction program and teachers in a district that uses a more traditional induction model. Participants’ scores on the Maslach Burnout Inventory – Educators Survey provided the dependent measures. There were, on average, no statistically significant differences (p < .05) in feelings of burnout of newly hired special education teachers in the two school districts. There were, on average, no statistically significant differences between the two groups. These findings suggest that, at least in these districts, special education teachers are staying in the field longer than originally expected, newly hired special education teachers are coming to the job better prepared, and deliberate and responsive induction programs did not influence feelings of burnout. The influence of participant demographic characteristics, particularly the amount of experience and licensure status, is discussed. Implications of these findings for special education teacher induction programs are suggested. Among these are the examination of supports from various sources, the availability of resources, and the structure of the induction program itself to meet the needs of more experienced teachers.
Keywords: Special Education; Induction Programs; Burnout; Retention; Attrition; Education, Special (0529); Education, Teacher Training (0530)